Effect of logging activities on water quality and benthic macroinvertebrate assemblages of Madek River Basin, Kluang, Johor, Malaysia - Aweng Eh Rak; Ismid Said; Maketab Mohamed; Ahmad Abas (2011)
The study was conducted to determine the effect of logging activities on water quality and benthic macroinvertebrate assemblages for the Madek River basin. The study area was situated in Kluang, Johor, Malaysia. Two sampling stations 500 meters apart are upstream and the other, downstream located at Madek River which flows through a logging area in Kluang Forest Reserve were identified. The sampling was conducted four (4) times from November 2008 to August 2009. Surber Net measuring 500 micron mesh size combined with a rectangular quadrat of 30 cm x 30 cm (0.09 m2) was used to sample the macroinvertebrates. The organisms were identified up to genus level except for Chironomidae which was only identified up to Sub-family level. For water quality, six in-situ parameters based on the standard procedure of U. S. Environmental Protection Agency were measured at each station. The parameters such as temperature, conductivity, dissolved oxygen (DO), pH, turbidity and salinity were measured using a multi parameter probe Model YSI 6920 with 650 MDS Display/Logger as well as a single parameter probe. All the physico-chemical water quality parameters were well below Class I as provided for under Interim National Water Quality Standards for Malaysia (INWQS), except turbidity which fell under Class II of the INWQS. There were only two (2) sensitive taxa namely Ephemeroptera and Trichoptera found in this station. Ephemeroptera that was found in the logging area was from genus Potamanthus, Pseudiron, Ephemerella and Rhithrogena, while Trichoptera was from genus Hydropsyche and Macrostemum. @JASEM